Emerging therapies for acute traumatic spinal cord injury - Jefferson R. Wilson; Nicole Forgione; Michael G. Fehlings (2012)
There are currently about 85 000 Canadians living with spinal cord injuries, more than half of which are secondary to trauma.[1][1] As the population ages, the incidence and prevalence of traumatic spinal cord injury are expected to increase, primarily as a result of fall-related injuries among